A quasi-analytical model of aluminized explosive products under strong constraint. (November 2017) - Duan, Ji; Wu, Cheng; An, Feng-Jiang; Liao, Sha-Sha
In this article, a simple model of aluminized explosive products under strong constraint is established. The analytical model incorporates the minimum details necessary to capture the contribution of the Al oxidation in the detonation products. In order to solve the flow field of aluminized explosive products analytically, some assumptions are necessary. It is assumed that Al particles are inert during the detonation reaction and do not affect the flow before oxidation of Al particles. To solve the flow field behind the detonation front analytically, the expansion process of detonation products is divided into several time ranges. In each short time range, it is assumed that the process is approximately isentropic. The metal plate test was conducted, and the motion of the metal plate was obtained. The comparison of calculation and test results was conducted. The quasi-analytic model can describe the contribution of Al reaction in the detonation products correctly, and the calculation results are in good agreement with test results.